THE IMPACT OF CONSUMERS' TRUST IN AN OFFLINE STORE ON THEIR BUYING INTENTION IN ITS ONLINE STORE - , Varsha Devi, Dr. Sahid Susilo Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The rise of Internet has created a new way of communicating and interacting not only with one and another but also with the online market place. However, with regard to online shopping, what is still attached to the consumer mind is the level of trust they addressed to the sellers on the Internet. The lack of trust by consumer is a significant barrier to the adoption of e-commerce. In this situation, previous research believes that consumerâs trust of a company may reduce any uncertainty that consumers have about online shopping. Adopted from previous research conducted by Hahn and Kim (2009), this research aims at examining the influence of consumer trust in an offline store on perceived confidence of shopping at the online store, information search intention at the online store, and behavioral intention to buy in the online store (online buying intention). This research also examines the influence of search intention for product information via the online store and perceived confidence of shopping at the online store on consumersâ behavioral intention to buy in the online store (online buying intention). The research object in this research is apparel click-andmortar stores in general, not limited to just one store. To collect the data, researcher uses questionnaires distributed to 200 respondents. The data is then analyzed by employing multiple regression analysis. The research findings conclude that consumer trust in an offline store has a positive and significant influence on perceived confidence of shopping at the online store, information search intention at the online store, and behavioral intention to buy in the online store. This research also shows that perceived confidence of shopping at the online store has a positive and significant influence on information search intention at the online store and behavioral intention to buy in the online store. Furthermore, this research also shows that information search intention at the online store has a positive and significant influence on behavioral intention to buy in the online store. These findings support previous research. At the end, this research provides some managerial implications for managers and some directions for future research who are interested in this topic. In addition, some limitations are also revealed.